The Use of Technology in Arabic Language Teaching: إستخدام التكنولوجية في تعليم اللغة العربية - Abdul Haris; Mohammad Misbahul Munir (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2021)
This article explores how technology can be used in the Arabic learning process. Depending on the situation different educational institutions face, other problems in Arabic learning can cause educators to change how they teach. This can be done through the development of information-rich technology and can be used anywhere to improve learning outcomes. The development of information technology has been very fast in recent years. At the same time, one field that feels or is affected is entirely meaningful by the development of this technology, namely the field of Education. The essence of education is providing information or communication between educators and students in the form of educational information. In contrast, educators are a source of information, media, ideas, and educational materials. Some parts of the elements of Education have a touch of educational technology so that e-learning learning arises. The problems raised in this study are 1) the introduction of Educational Technology, 2) the development of Educational Technology, and 3) the relationship between educational technology. The research methods are a literature review (Library Research) and descriptive qualitative. This study examines the theoretical analysis of the use of educational technology in Arabic language learning. Data collection methods used by researchers in this study are observation, interviews, and documentaries. In this study, researchers used a triangulation approach for data validity. The results of this study are as follows: 1) technologies that can be used in Arabic language learning, 2) disadvantages and advantages of using Arabic Language Learning Technology, 3) Steps and efforts to overcome the problems of Arabic language learning and learning technology. تستكشف هذه المقالة عن أهمية في استخدام التكنولوجية في عملية تعلم اللغة العربية. اعتمادًا على الموقف الذي تواجهه المؤسسات التعليمية المختلفة، يمكن أن تؤدي المشكلات الأخرى في تعليم اللغة العربية إلى تغيير المعلمين لطريقة التدريس. يمكن القيام بذلك من خلال تطوير تكنولوجية بالمعلومات و يمكن استخدامها في أي مكان لتحسين نتائج التعليم. لقد كان تطور تكنولوجية و المعلومات سريعًا في السنوات الأخيرة ، كما هو الحال في أحد المجالات التي شعرت أو كانت ذات مغزى كبير مع هذا التطور التكنولوجي هو التعليم أي التربية. التعليم هو عملية توفير المعلومات أو الاتصال بين المعلمين و الطلاب بمعلومات تعليمية ، في حين أن المعلمين هم مصدر للمعلومات، و الوسائل والأفكار والمواد التعليمية ، وبعض أجزاء التعليم تحصل على لمسة من التكنولوجيا التعليمية حتى يظهر التعلم الإلكتروني .والمشكلة البحث هي: 1) ما هي مقدمة في تكنولوجية التعليم، 2) كيف يتم تطوير تكنولوجية التعليم، 3) ما هي العلاقة بين تكنولوجية التعليم والتعليم. أما منهجية البحث التي يتمسك بها الباحث تأتي بمدخل كيفي ونوع دراسة مكتبية ثم تأكيدا بتحليل المحتويات بطريقة جمع البيانات الثلاث بدءا من الملاحظة ومرورا بالمقابلة الشخصية، حلل هذا البحث عن دراسة النظرية عن تكنولوجية التعليم في تعليم اللغة العربية. وأما مناهج جمع البيانات التي يستخدمه الباحث في هذا البحث فهي الملاحظة والمقابلة الشخصية والوثائقية. وتحليل البيانات الذي يستخدم الباحث في هذا البحث المنهج التثليثي لصحة البيانات. و نتائج هذه الدراسة كما يلي: 1) أنواع التكنولوجية يمكن استخدامها في تعليم اللغة العربية 2) العيوب والمزايا في استخدام تكنولوجية التعليم اللغة العربية 3) الخطوات والجهود ليحلّل من المشكلات في تعليم اللغة العربية و التكنولوجيتها .